Implementasi Perpanjangan Perjanjian Kerja Waktu Tertentu (PKWT) bagi Pekerja Kontrak Pada Koperasi Yowana Bakti Mandiri Desa Jagapati Kabupaten Badung - I Made Wiratama; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Warmadewa Press, 2022)
This study aims to find out about the legal responsibilities of employers who default on workers in relation to Law Number 13 of 2003 concerning Manpower. Certain time work agreements (PKWT) are widely used by entrepreneurs/companies because they are considered very efficient in carrying out company operations and can minimize expenses for a company or cooperative. The employment agreement is the beginning of the birth of the working relationship between the employer and the worker. This research uses empirical legal research. The Yowana Bakti Mandiri Cooperative still does not comply with several provisions of the applicable laws and regulations, namely extending a certain time work agreement more than 1 (one) time and not giving a 30-day lag when renewing the agreement, and requiring a probationary period for contract workers.